Export Take-Offs and Acceleration: Unpacking Cross-Sector Linkages in the Evolution of Comparative Advantage - Dany Bahar; Samuel Rosenow; Ernesto Stein; Rodrigo Wagner (Center for Economic Studies and ifo Institute (CESifo), 2018)
The transition into non-traditional export activities attracts important policy and academic attention. Using international trade data, we explore how alternative linkages relate to the take-off and acceleration of export industries. Concretely, we run a horse-race among alternative Marshallian linkages across sectors: input-output relations, technology and labor. Technology has a predictive power depending on the specification used. We consistently find, however, that export take-offs are more likely to occur in sectors that are upstream to already competitive export industries. Our findings, which are mostly driven by developing economies, are consistent with Albert Hirschman's 60-year-old view that the forces behind upstream linkages fueled the growth of new competitive industries in the developing world.
Keywords: O14; O33; F14; 330; relatedness; comparative advantage; patents; labor; upstream; downstream